Work Engagement and Demographic Variables: A Study of State Universities of Haryana - Sharma, Anju (Innovative Research Thoughts, 2020)
The study investigated the relationship between respondents‘work engagement and personal or demographic variables like faculty work area, type of institution, , designation, total experience, , age, gender, educational background, monthly salary etc. Work engagement was considered as dependent variable and demographic variables were considered as independent variables. In the current study the dependent variable namely work engagement was measured as a scale variable and all independent variables namely the personal variables were measured as categorical variables. Hence, the difference in mean work engagement across the samples categorized on the basis of personal variables was analyzed using one-way analysis of variance (ANOVA) and WELCH test on the basis of levene test value that is related to check the homogenity of variance. It was found that work engagement of faculty members varies significantly with faculty work area/ discipline, designation, total experience, age, educational background and salary.